MANAGEMENT OF DIABETIC FOOT - TWO YEARS EXPERIENCE - Zafar, Arshad (Journal of Ayub Medical College Abbottabad, 2001)
Background: Diabetic foot is a serious complication of diabetes mellitus and may be the initial presentation of undiagnosed diabetes mellitus. A study of 48 patients with diabetic foot admitted in Surgical B Unit of Ayub Teaching Hospital over a period of two years is presented here. Methods: This study was done to identify the risk factors and causative organisms in diabetic foot. This will help to lay down important principles of management of diabetic foot and highlight problems faced in the management of diabetic foot in our set up. Results: There were 32 (66.6%) males and 16 (33.3%) females. The age incidence ranged from 30-70 years. Average length of hospital stay was 26 days. 2 patients had cellulitis. 6 patients had gangrene. 10 patients had ulcers and 15 patients had abscesses. 31 (64%) patients were cured by drainage of abscess and debridements alone. 17(36%) patients needed amputations. Peripheral neuropathy was the commonest risk factor. Staphylococcus aureus was the most common organism isolated from cultures (54%). Conclusions: Early hospitalization, effective glycaemic control, aggressive debridements and patient education in foot care can minimize diabetic foot diseases.